PERIPHERAL SENSORY PERCEPTION OF DIABETIC USING SEMMES WEINSTEIN 5.07 MONOFILAMENT (Journal of Biomedical Investigation, 2015)
Gradual loss of sensation in the foot is a major consequence of diabetes mellitus. It is a precursor to foot ulcers, which may necessitate amputation eventually. Early detection of peripheral sensory loss in the foot would help to prevent further complications. In developed countries the ability to perceive 5.07 monofilament is accepted as normal, but in Nigeria the assessment of peripheral sensory perception with 5.07 monofilament method is not common. The aim of this study was to compare peripheral! sensory perception (PSP) in patients with diabetes and apparently healthy controls without diabetes. Subjects were 100 and were diagnosed as having diabetes mellitus and 100 apparently healthy controls. The subjects were recruited using purposive non-probability sampling technique. The design was ex-post facto research design. The sensation was tested on eleven pressure points on the sole and dorsum of the right foot using 5.07 semmes Weinstein monofilament in all the subjects. Data were analyzed using independent student t-test to compare the scores between Group I and II subjects. The effect of gender on peripheral sensory perception in each group was analyzed using the independent student t-test. One way analysis of variance was used to determine if peripheral sensory perception scores of subjects in each group differed significantly across the age groups. Level of significant was set at 0.05. Results showed that 71% of subjects with diabetes had intact sensation and 29% had impaired sensation. While 95% control subjects had intact sensation and 4% had impaired sensation. Subjects with diabetes had significantly lower peripheral sensory perception than the control subjects (p0.05). It was concluded that peripheral sensory perception was significantly lower in subjects with diabetes than in apparently healthy control subjects. The gender or age of the subject had no significant effect on peripheral sensory perception. The use of semmes Weinstein 5.07 monofilament is recommended for preliminary diagnosis of peripheral neuropathy in subjects with diabetes. Also, more studies involving subjects with peripheral neuropathy and studies of other monofilament sizes as well as data on associated risk factors such as duration of diabetes, smoking habits, and height of diabetics are advocated.
Keywords: Diabetics; Non-diabetics; Semmes-Weinstein 5.07 monofilament; Sensation